Beam Expansion of Blind Spot Detection Radar Antennas Using a Radome with Defected Corrugated Inner Wall - Hayeon Kim; Haengseon Lee; Jeonghoon Cho; Cheolbok Kim (International Journal of Antennas and Propagation)
A beam expanding radome for 76.5 GHz automotive radar antennas is presented whose inner surface is engraved with corrugations. The radar used for blind spot detection (BSD) requires a very wide beam width to ensure longer time for tracking out-of-sight objects. It is found that the corrugations modulate the phase velocities of the waves along the surface, which increases beam width in the far field. In addition, defects in the corrugation increase beam width even further. The presented structure satisfies the beam width requirement while keeping a low profile.